A wear-resistant high-strength composite polyurethane sieve plate and preparation method thereof
By cross-linking reaction of modified polyurethane with modified alumina powder and epoxy resin, and adding modified nylon fibers, the problems of insufficient wear resistance, mechanical strength and acid and alkali corrosion resistance of the polyurethane screen are solved, and its overall performance is significantly improved.
Patent Information
- Application Number
- CN202510063959.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-15
AI Technical Summary
The wear resistance, mechanical strength and strong acid and alkali corrosion resistance of existing polyurethane screens need to be improved.
By reacting modified polyurethane with olefin double bond modified modified alumina powder and catalyst, a complex crosslinking network structure is formed; then epoxy resin and modified nylon fiber are added, and the hardness and mechanical strength of the screen plate are improved through high-temperature treatment and physical interlacing crosslinking, and its acid and alkali corrosion resistance is enhanced.
It significantly improves the wear resistance, mechanical strength and strong acid and alkali corrosion resistance of polyurethane screen plates, and extends its service life.
Smart Images

Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyurethane sieve plate processing, and in particular to a wear-resistant high-strength composite polyurethane sieve plate and a preparation method thereof. Background Art
[0002] Polyurethane sieve plate is a mesh sieve plate product made of polyurethane as raw material. Compared with stainless steel welded sieve plates, it has the characteristics of long service life and excellent high wear resistance, high elasticity, sound absorption, and vibration reduction.
[0003] The prior art, an invention patent with publication number CN115160768A, discloses a method for preparing an MDI wear-resistant screen plate, which adopts a prepolymer method to prepare a high-efficiency polyurethane screen plate casting material for a slurry with polyether polyol, MDI, and modified MDA, and obtains a polyurethane screen plate with good wear resistance, oil resistance, hydrolysis resistance, and aging resistance by modifying and chain extending MDA. In the presence of media such as water and oil, the friction coefficient between the polyurethane and the material is reduced, and the process operability of the reaction injection molding casting polyurethane screen plate is improved to solve the problem of poor compatibility between the polyurethane prepolymer and diphenylmethane, and the prepared elastomer has a uniform structure and improved mechanical properties.
[0004] However, the wear resistance of the polyurethane sieve plate material in the prior art is directly related to its hardness. Generally, the higher the hardness of the polyurethane sieve plate, the better its wear resistance. However, the degree of cross-linking between polyurethane sieve plate molecules is often low. Affected by the compatibility between molecules, the mechanical strength of the polyurethane sieve plate material needs to be further improved. At the same time, the polyurethane material has good stability to acidic and alkaline solutions, but for acids or alkalis with high concentrations, the tolerance of the polyurethane material is often poor, especially for materials with low degree of cross-linking between molecules. Corrosive liquids can easily penetrate into the interior of the material from the gaps between molecules, resulting in changes in the overall strength of the material, especially the softening of the surface of the material, which makes the surface of the sieve plate prone to wear and damage during screening.
[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0006] The purpose of the present invention is to provide a wear-resistant high-strength composite polyurethane sieve plate and a preparation method thereof, so as to solve the technical problem that the wear resistance, mechanical strength and strong acid and alkali corrosion resistance of the polyurethane sieve plate in the prior art need to be further improved.
[0007] The purpose of the present invention can be achieved by the following technical scheme: A method for preparing a wear-resistant high-strength composite polyurethane sieve plate comprises the following steps:
[0008] S1. Add the modified polyurethane to xylene, raise the temperature of the reaction system to 90-100°C, stir until the system is dissolved, add the modified alumina powder modified with olefin double bonds and the catalyst to the reaction system, keep the temperature for 6-8h, and post-treat to obtain a composite polyurethane solution with a solid content of 45-55%;
[0009] The synthetic reaction mechanism of the composite polyurethane solution is:
[0010] During the reaction, under the action of catalyst and high temperature, the silicon-hydrogen positions on the polysiloxane block in the modified polyurethane undergo silylation with the modified alumina powder modified with olefin double bonds, forming a complex cross-linked network structure with the alumina powder as the cross-linking potential, and preparing a composite polyurethane composed of alumina powder and modified polyurethane.
[0011] S2, adding epoxy resin solution to the composite polyurethane solution, stirring for 20-30 minutes, and post-processing to obtain a casting material precursor;
[0012] S3, heating the castable precursor until the system is melted, adding modified nylon fiber to the castable precursor, stirring and mixing for 3-5 minutes to obtain a castable;
[0013] S4. Raise the temperature of the sieve plate mold to 175-185°C, pour the casting material into the mold, close the mold after degassing, raise the mold pressure to 1-2MPa, keep the temperature and pressure to cure for 8-10 minutes, and then discharge the material to obtain a composite polyurethane sieve plate.
[0014] Furthermore, in step S1, the amount ratio of the modified polyurethane, xylene, modified alumina powder and catalyst is 10g:80mL:1g:0.01g, the catalyst is chloroplatinic acid, and the post-treatment includes: after the reaction is completed, the temperature of the reaction system is reduced to room temperature, the reaction solution is washed 3 times with purified water, and after the organic phase is dried, part of the solvent is evaporated under reduced pressure in an evaporator at 80-90°C to obtain a 45-55% composite polyurethane solution.
[0015] Furthermore, in step S2, the volume ratio of the composite polyurethane solution to the epoxy resin solution is 8:7, the epoxy resin solution is composed of o-cresol epoxy resin and xylene in a dosage ratio of 2g:5mL, and the post-treatment includes: after the reaction is completed, the reaction system is kept warm at 80-90°C, the solvent and low-boiling substances are evaporated under reduced pressure, and the material is discharged while hot to obtain a casting material precursor.
[0016] Furthermore, in step S3, the weight ratio of the casting material precursor to the modified nylon fiber is 70:5-8.
[0017] Furthermore, the preparation method of the modified polyurethane is as follows: under the protection of inert gas, hydroxyl-terminated polysiloxane, polytetramethylene glycol, and a catalyst are added to xylene and stirred, the temperature of the reaction system is increased to 65-75°C, a diisocyanate solution is added dropwise to the reaction system, and after the addition is completed, the reaction is kept warm for 2-3 hours to obtain a polyurethane prepolymer solution, a chain extender is added to the polyurethane prepolymer solution, the reaction is kept warm for 60-80 minutes, a capping agent is added to the reaction system, the reaction is kept warm for 90-120 minutes, and the modified polyurethane is obtained by post-treatment.
[0018] The synthetic reaction mechanism of modified polyurethane is:
[0019] During the reaction, under the promotion of the catalyst, the amount of the diisocyanate solution is controlled, and the isocyanate groups in the diisocyanate solution and the alcohol hydroxyl groups on the hydroxyl-terminated polysiloxane and polytetrahydrofuran ether diol molecules undergo condensation reaction to form a polyurethane prepolymer with co-blocking of polysiloxane and polytetrahydrofuran, the hydroxyl groups on the chain extender molecules undergo condensation with the isocyanate groups on the polyurethane prepolymer molecules, and the crosslinking degree of the polyurethane prepolymer molecular chain is improved, ethanolamine is used as the end-capping agent, and the amino groups on the end-capping agent molecules react with the isocyanate groups on the cross-linked polyurethane chains to form end-capping groups, and the modified polyurethane is prepared, and the reaction is ensured to be complete by controlling the excess of the end-capping agent, and the small molecule end-capping agent is selected to facilitate separation from the polyurethane in the subsequent distillation process, thereby simplifying the preparation process.
[0020] Furthermore, the amount ratio of the hydroxyl-terminated polysiloxane, polytetramethylene glycol, catalyst and xylene is 3g:7g:0.1g:30mL, the catalyst is dibutyltin dilaurate, the diisocyanate solution is composed of isophorone diisocyanate and xylene in an amount ratio of 1g:2mL, during the synthesis of the polyurethane prepolymer, the molar ratio of isocyanate to hydroxyl is 1.1:1, the amount ratio of the hydroxyl-terminated polysiloxane, chain extender and end-capping agent is 6g:1-1.5g:3g, the chain extender is 1,2,4-butanetriol, and the end-capping agent is ethanolamine, and the post-treatment includes: after the reaction is completed, the temperature of the reaction system is increased to 80-90°C, and the solvent is evaporated under reduced pressure to obtain the modified polyurethane.
[0021] Furthermore, the preparation method of hydroxyl-terminated polysiloxane is as follows: cyclotetramethylsiloxane, trifluoropropylmethylcyclotrisiloxane, octamethylcyclotetrasiloxane and a catalyst are added to xylene and stirred, the temperature of the reaction system is increased to 115-125°C, and the reaction is kept warm for 2-3 hours, 1,3-bis(3-hydroxypropyl)-1,1,3,3-tetramethyldisiloxane is added to the reaction system, the reaction is kept warm for 3-4 hours, and the hydroxyl-terminated polysiloxane is obtained by post-treatment.
[0022] The synthetic reaction mechanism of hydroxyl-terminated polysiloxane is:
[0023] During the reaction, cyclotetradimethylsiloxane, trifluoropropylmethylcyclotrisiloxane, and octamethylcyclotetrasiloxane are used as siloxane monomers, which are hydrolyzed under high temperature and catalyst to form linear siloxane chains with disilanols. Subsequently, silanols undergo condensation reaction to form silicon-oxygen-silicon bonds to generate polysiloxane chains. 1,3-bis(3-hydroxypropyl)-1,1,3,3-tetramethyldisiloxane is used as a capping agent, which is hydrolyzed under the action of catalyst and high temperature as the capping group of the polysiloxane chain, forming alcohol hydroxyl modification on the polysiloxane chain to prepare hydroxyl-terminated polysiloxane.
[0024] Furthermore, the amount ratio of the cyclotetrasiloxane, trifluoropropylmethylcyclotrisiloxane, octamethylcyclotetrasiloxane and 1,3-bis(3-hydroxypropyl)-1,1,3,3-tetramethyldisiloxane is 3 mol:2 mol:5 mol:1 mol, the amount ratio of the octamethylcyclotetrasiloxane, the catalyst and xylene is 1 g:0.5 g:10 mL, the catalyst is 55-60 wt % sulfuric acid, and the post-treatment comprises: after the reaction is completed, the temperature of the reaction system is lowered to room temperature, the reaction system is washed with purified water to neutrality and then separated, the organic phase is dried, and xylene and low-boiling impurities are removed under reduced pressure in an evaporator at 80-90° C. to obtain a hydroxyl-terminated polysiloxane.
[0025] Furthermore, the preparation method of modified alumina powder is as follows: nano alumina powder and KH-570 are added to anhydrous ethanol and ultrasonically dispersed for 30-50 minutes, the reaction system is stirred, the temperature of the reaction system is increased to 50-60°C, a catalyst is added to the reaction system, the reaction is kept warm for 60-80 minutes, and the modified alumina powder is obtained by post-treatment.
[0026] The synthetic reaction mechanism of modified alumina powder is:
[0027] During the reaction, the siloxane bonds on the KH-570 molecules are hydrolyzed in an alkaline environment to form highly reactive silanol groups, which condense with the surface of the nano-alumina to form a coating of KH-570 molecules on the outside of the nano-alumina, thereby preparing modified alumina powder modified with olefin double bonds.
[0028] Furthermore, the dosage ratio of the nano alumina powder, KH-570, anhydrous ethanol and catalyst is 5g:2g:50mL:8mL, the catalyst is 2-3mol / L sodium hydroxide solution, and the post-treatment includes: after the reaction is completed, the temperature of the reaction system is lowered to room temperature, filtered, the filter cake is washed with purified water until it is neutral and then dried, the filter cake is transferred to a drying oven at a temperature of 65-75°C, and vacuum dried to constant weight to obtain modified alumina powder.
[0029] Furthermore, the preparation method of the modified nylon fiber is: adding nylon fiber and dopamine hydrochloride into deionized water for ultrasonic dispersion, adding tris(hydroxymethyl)aminomethane hydrochloride) to the reaction system, adjusting the pH of the system to 8.5, reacting at room temperature for 20-24 hours, and post-treating to obtain the modified nylon fiber.
[0030] The synthetic reaction mechanism of modified nylon fiber is:
[0031] During the reaction process, the nylon fiber and dopamine hydrochloride are premixed and then the pH of the system is adjusted to alkaline using tris(hydroxymethyl)aminomethane hydrochloride) to promote the oxidative polymerization reaction of dopamine hydrochloride and form a dopamine coating layer on the surface of the nylon fiber to prepare the modified nylon fiber.
[0032] Furthermore, the dosage ratio of the nylon fiber, dopamine hydrochloride and deionized water is 5g:3-4g:60mL, and the post-treatment includes: after the reaction is completed, filtering, washing the filter cake with purified water until it is neutral and then drying, transferring the filter cake to a drying oven at a temperature of 70-80°C, and vacuum drying to constant weight to obtain modified nylon fiber.
[0033] The invention also provides a wear-resistant high-strength composite polyurethane sieve plate, which is prepared by adopting a preparation method of the wear-resistant high-strength composite polyurethane sieve plate.
[0034] The present invention has the following beneficial effects:
[0035] 1. The wear-resistant high-strength composite polyurethane sieve plate of the present invention is prepared by mixing composite polyurethane and o-cresol epoxy resin. During the mixing process, the molecular chains of the o-cresol epoxy resin are physically interlaced with the composite polyurethane having a complex cross-linked network. The castable precursor composed of the composite polyurethane and the o-cresol epoxy resin is then reinforced with a modified nylon fiber coated with polydopamine. After high-temperature treatment, the ring-opening condensation of the epoxy groups on the o-cresol epoxy resin molecules is promoted, thereby improving the cross-linking degree of the polyurethane sieve plate material, thereby improving the wear resistance and mechanical strength of the polyurethane sieve plate material.
[0036] 2. The wear-resistant high-strength composite polyurethane sieve plate of the present invention is reinforced by using modified alumina powder modified with olefin double bonds to strengthen the modified polyurethane having co-embedded cross-linked polysiloxane chains and polytetramethylene glycol chains, thereby improving the crosslinking degree of the composite polyurethane, forming physical and chemical crosslinking points in the polyurethane sieve plate material, and improving the hardness and mechanical strength of the sieve plate. The polysiloxane chain segment has excellent lubricity and wear resistance, reduces energy loss during friction, and protects the polyurethane matrix from wear. Polytetramethylene glycol serves as a soft segment to increase the flexibility and elasticity of the polyurethane, and helps to absorb and disperse energy during friction. The modified alumina powder serves as a hard filler to resist external wear and improve the wear resistance of the polyurethane sieve plate. In addition, polysiloxane itself has good chemical stability. By introducing silicon-fluorine chains into its molecular chain, its ability to resist erosion by chemical substances such as acids and alkalis is improved, so that its modified alumina cooperates with each other, further improving the chemical corrosion resistance of the polyurethane sieve plate.
[0037] 3. The wear-resistant high-strength composite polyurethane sieve plate of the present invention can promote the mixing of o-cresol epoxy resin and composite polyurethane to form physical interlaced crosslinking by mixing o-cresol epoxy resin and composite polyurethane by a solution method. The o-cresol epoxy resin itself has high hardness and rigidity, and its rigid molecular chain is interlaced in the molecular network of polyurethane to form physical crosslinking points, thereby increasing the hardness and wear resistance of the polyurethane sieve plate, and the o-cresol epoxy resin itself has good acid and alkali corrosion resistance, and it cooperates with the composite polyurethane to further improve the acid and alkali corrosion resistance of the polyurethane sieve plate. By coating and modifying the nylon fiber, it can be evenly dispersed in the castable precursor to improve the mechanical strength of the material, and the modified nylon fiber and the active groups such as the amino group or terminal hydroxyl group on the molecular chain of the composite polyurethane can condense with the epoxy group on the o-cresol epoxy resin molecule under a high temperature environment, further improving the degree of crosslinking between molecules, thereby further improving the overall performance of the polyurethane sieve plate. DETAILED DESCRIPTION
[0038] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] The polytetramethylene glycol in the present invention is polytetramethylene glycol-1000;
[0040] The o-cresol epoxy resin in the present invention is selected from Sinopec, has an epoxy equivalent of 200-215, and a softening point of 80-90°C;
[0041] The nylon fiber in the present invention is nylon 66 fiber, and the melting point is 250-270°C.
[0042] Example 1
[0043] This embodiment provides a method for preparing a wear-resistant high-strength composite polyurethane screen plate, comprising the following steps:
[0044] S1. Preparation of hydroxyl-terminated polysiloxane
[0045] Weigh: 55.3 g of cyclotetramethylsiloxane, 93.7 g of trifluoropropylmethylcyclotrisiloxane, 148.3 g of octamethylcyclotetrasiloxane, 74.2 g of 55 wt% sulfuric acid and 1483 mL of xylene, add them into a three-necked flask and stir, raise the temperature of the three-necked flask to 115°C, keep warm for 2 hours, add 25.1 g of 1,3-bis(3-hydroxypropyl)-1,1,3,3-tetramethyldisiloxane into the three-necked flask, keep warm for 3 hours, lower the temperature of the three-necked flask to room temperature, add 500 mL of purified water into the three-necked flask, let stand for separation, wash the organic phase with purified water until neutral and then separate the liquids, dry the organic phase with anhydrous sodium sulfate for 2 hours, filter, transfer the filtrate to a rotary evaporator with a water bath temperature of 80°C, evaporate xylene and low-boiling impurities under reduced pressure to obtain hydroxyl-terminated polysiloxane.
[0046] S2. Preparation of modified polyurethane
[0047] Isophorone diisocyanate and xylene were mixed evenly at a ratio of 1 g:2 mL to obtain a diisocyanate solution for later use;
[0048] Weigh: 90 g of hydroxyl-terminated polysiloxane, 210 g of polytetramethylene glycol, 3 g of dibutyltin dilaurate and 900 mL of xylene, add into a three-necked flask protected by nitrogen and stir, raise the temperature of the three-necked flask to 65° C., add diisocyanate solution dropwise into the three-necked flask at a molar ratio of isocyanate to hydroxyl of 1.1:1, and after the addition is complete, heat and react for 2 h to obtain a polyurethane prepolymer solution;
[0049] 15 g of 1,2,4-butanetriol was added to a three-necked flask containing a polyurethane prepolymer solution, and the reaction was kept warm for 60 min. 45 g of ethanolamine was added to the reaction system, and the reaction was kept warm for 90 min. The temperature of the three-necked flask was increased to 80° C., and the solvent was evaporated under reduced pressure to obtain a modified polyurethane.
[0050] S3. Preparation of composite polyurethane solution
[0051] Weigh: 50g of nano-alumina powder, 20g of KH-570 and 500mL of anhydrous ethanol, add them into a three-necked flask, ultrasonically disperse for 30min, transfer the three-necked flask to a water bath with mechanical stirring, raise the temperature of the three-necked flask to 50°C, add 80mL of 2mol / L sodium hydroxide solution to the reaction system, keep warm and react for 60min, lower the temperature of the three-necked flask to room temperature, filter, wash the filter cake with purified water until it is neutral, and then drain, transfer the filter cake to a drying oven at a temperature of 65°C, and vacuum dry to constant weight to obtain modified alumina powder;
[0052] Weigh: 100 g of modified polyurethane and 800 mL of xylene are added to a three-necked flask and stirred. The temperature of the three-necked flask is raised to 90°C and stirred until the system is dissolved. 10 g of modified alumina powder and 0.1 g of chloroplatinic acid are added to the three-necked flask, and the reaction is kept warm for 6 hours. The temperature of the three-necked flask is lowered to room temperature, 400 mL of purified water is added to the three-necked flask and stirred for 10 minutes. The organic phase is allowed to stand and separate. The organic phase is washed 3 times with purified water, and the organic phase is dried over anhydrous sodium sulfate for 2 hours and then filtered. The filtrate is transferred to a rotary evaporator with a water bath temperature of 80°C, and part of the solvent is evaporated under reduced pressure to obtain a 45% composite polyurethane solution.
[0053] S4. Preparation of modified nylon fiber
[0054] Weigh: 50 g of nylon fiber, 30 g of dopamine hydrochloride, and 600 mL of deionized water, add them into a three-necked flask for ultrasonic dispersion, add tris(hydroxymethyl)aminomethane hydrochloride) into the three-necked flask, adjust the system pH to 8.5, stir and react at room temperature for 20 hours, filter, wash the filter cake with purified water until it is neutral and then dry, transfer the filter cake to a drying oven at a temperature of 70°C, and vacuum dry it to constant weight to obtain modified nylon fiber.
[0055] S5. Preparation of casting material
[0056] Add o-cresol epoxy resin and xylene in a ratio of 2g:5mL into a three-necked flask and stir, raise the temperature of the three-necked flask to 80°C, stir until the system is dissolved, cool to room temperature, and obtain an epoxy resin solution for later use;
[0057] The composite polyurethane solution and the epoxy resin solution were added into a three-necked flask in a volume ratio of 8:7 and stirred for 20 minutes. The temperature of the three-necked flask was raised to 80° C., the solvent and low-boiling substances were evaporated under reduced pressure, and the material was discharged while hot to obtain a castable precursor.
[0058] S6. Preparation of polyurethane sieve plate
[0059] Weigh: 700 g of a casting material precursor is heated until it is melted, 50 g of modified nylon fiber is added to the casting material precursor, and stirred and mixed for 3 minutes to obtain a casting material;
[0060] The temperature of the sieve plate mold is increased to 175°C, and the molten casting material is poured into the mold. The mold is closed after degassing, and the mold pressure is increased to 1MPa. The material is cured by heat preservation and pressure maintenance for 8 minutes to obtain a composite polyurethane sieve plate.
[0061] Example 2
[0062] This embodiment provides a method for preparing a wear-resistant high-strength composite polyurethane screen plate, comprising the following steps:
[0063] S1. Preparation of hydroxyl-terminated polysiloxane
[0064] Weigh: 55.3 g of cyclotetramethylsiloxane, 93.7 g of trifluoropropylmethylcyclotrisiloxane, 148.3 g of octamethylcyclotetrasiloxane, 74.2 g of 57 wt% sulfuric acid and 1483 mL of xylene, add them into a three-necked flask and stir, raise the temperature of the three-necked flask to 120°C, keep warm for 2.5 hours, add 25.1 g of 1,3-bis(3-hydroxypropyl)-1,1,3,3-tetramethyldisiloxane into the three-necked flask, keep warm for 3.5 hours, lower the temperature of the three-necked flask to room temperature, add 500 mL of purified water into the three-necked flask, let stand for separation, wash the organic phase with purified water until neutral and then separate the liquids, dry the organic phase with anhydrous sodium sulfate for 2.5 hours, filter, transfer the filtrate to a rotary evaporator with a water bath temperature of 85°C, evaporate xylene and low-boiling impurities under reduced pressure to obtain hydroxyl-terminated polysiloxane.
[0065] S2. Preparation of modified polyurethane
[0066] Isophorone diisocyanate and xylene were mixed evenly at a ratio of 1 g:2 mL to obtain a diisocyanate solution for later use;
[0067] Weigh: 90 g of hydroxyl-terminated polysiloxane, 210 g of polytetramethylene glycol, 3 g of dibutyltin dilaurate and 900 mL of xylene, add into a three-necked flask protected by nitrogen and stir, raise the temperature of the three-necked flask to 70° C., add diisocyanate solution dropwise into the three-necked flask at a molar ratio of isocyanate to hydroxyl of 1.1:1, and after the addition is complete, keep warm for 2.5 hours to obtain a polyurethane prepolymer solution;
[0068] 18.8 g of 1,2,4-butanetriol was added to a three-necked flask containing a polyurethane prepolymer solution, and the reaction was kept warm for 70 min. 45 g of ethanolamine was added to the reaction system, and the reaction was kept warm for 105 min. The temperature of the three-necked flask was increased to 85° C., and the solvent was evaporated under reduced pressure to obtain a modified polyurethane.
[0069] S3. Preparation of composite polyurethane solution
[0070] Weigh: 50g of nano-alumina powder, 20g of KH-570 and 500mL of anhydrous ethanol, add them into a three-necked flask, ultrasonically disperse for 40min, transfer the three-necked flask to a water bath with mechanical stirring, raise the temperature of the three-necked flask to 55°C, add 80mL of 2.5mol / L sodium hydroxide solution to the reaction system, keep warm for 70min, lower the temperature of the three-necked flask to room temperature, filter, wash the filter cake with purified water until it is neutral, and then drain, transfer the filter cake to a drying oven at a temperature of 70°C, and vacuum dry to constant weight to obtain modified alumina powder;
[0071] Weigh: 100 g of modified polyurethane and 800 mL of xylene are added to a three-necked flask and stirred. The temperature of the three-necked flask is raised to 95°C and stirred until the system is dissolved. 10 g of modified alumina powder and 0.1 g of chloroplatinic acid are added to the three-necked flask, and the reaction is kept warm for 7 hours. The temperature of the three-necked flask is lowered to room temperature, 400 mL of purified water is added to the three-necked flask and stirred for 13 minutes. The organic phase is allowed to stand and separate. The organic phase is washed 3 times with purified water, and the organic phase is dried over anhydrous sodium sulfate for 2.5 hours and then filtered. The filtrate is transferred to a rotary evaporator with a water bath temperature of 85°C, and part of the solvent is evaporated under reduced pressure to obtain a 50% composite polyurethane solution.
[0072] S4. Preparation of modified nylon fiber
[0073] Weigh: 50 g of nylon fiber, 35 g of dopamine hydrochloride, and 600 mL of deionized water, add them into a three-necked flask for ultrasonic dispersion, add tris(hydroxymethyl)aminomethane hydrochloride) into the three-necked flask, adjust the system pH to 8.5, stir and react at room temperature for 22 hours, filter, wash the filter cake with purified water until it is neutral and then dry, transfer the filter cake to a drying oven at a temperature of 75°C, and vacuum dry it to constant weight to obtain modified nylon fiber.
[0074] S5. Preparation of casting material
[0075] Add o-cresol epoxy resin and xylene in a ratio of 2g:5mL into a three-necked flask and stir, raise the temperature of the three-necked flask to 85°C, stir until the system is dissolved, cool to room temperature, and obtain an epoxy resin solution for later use;
[0076] The composite polyurethane solution and the epoxy resin solution were added into a three-necked flask in a volume ratio of 8:7 and stirred for 25 minutes. The temperature of the three-necked flask was raised to 85° C., the solvent and low-boiling substances were evaporated under reduced pressure, and the material was discharged while hot to obtain a casting material precursor.
[0077] S6. Preparation of polyurethane sieve plate
[0078] Weigh: 700 g of a casting material precursor is heated until it is melted, 65 g of modified nylon fiber is added to the casting material precursor, and stirred and mixed for 4 minutes to obtain a casting material;
[0079] The temperature of the sieve plate mold is increased to 180°C, and the molten casting material is poured into the mold. The mold is closed after degassing, and the mold pressure is increased to 1.5MPa. The material is cured by heat preservation and pressure preservation for 9 minutes to obtain a composite polyurethane sieve plate.
[0080] Example 3
[0081] This embodiment provides a method for preparing a wear-resistant high-strength composite polyurethane screen plate, comprising the following steps:
[0082] S1. Preparation of hydroxyl-terminated polysiloxane
[0083] Weigh: 55.3 g of cyclotetramethylsiloxane, 93.7 g of trifluoropropylmethylcyclotrisiloxane, 148.3 g of octamethylcyclotetrasiloxane, 74.2 g of 60 wt% sulfuric acid and 1483 mL of xylene, add them into a three-necked flask and stir, raise the temperature of the three-necked flask to 125°C, keep warm for 3 hours, add 25.1 g of 1,3-bis(3-hydroxypropyl)-1,1,3,3-tetramethyldisiloxane into the three-necked flask, keep warm for 4 hours, lower the temperature of the three-necked flask to room temperature, add 500 mL of purified water into the three-necked flask, let stand for separation, wash the organic phase with purified water until neutral and then separate the liquids, dry the organic phase with anhydrous sodium sulfate for 3 hours, filter, transfer the filtrate to a rotary evaporator with a water bath temperature of 90°C, evaporate xylene and low-boiling impurities under reduced pressure to obtain hydroxyl-terminated polysiloxane.
[0084] S2. Preparation of modified polyurethane
[0085] Isophorone diisocyanate and xylene were mixed evenly at a ratio of 1 g:2 mL to obtain a diisocyanate solution for later use;
[0086] Weigh: 90 g of hydroxyl-terminated polysiloxane, 210 g of polytetramethylene glycol, 3 g of dibutyltin dilaurate and 900 mL of xylene, add into a three-necked flask protected by nitrogen and stir, raise the temperature of the three-necked flask to 75° C., add diisocyanate solution dropwise into the three-necked flask at a molar ratio of isocyanate to hydroxyl of 1.1:1, and after the addition is complete, heat and react for 3 h to obtain a polyurethane prepolymer solution;
[0087] 22.5 g of 1,2,4-butanetriol was added to a three-necked flask containing a polyurethane prepolymer solution, and the reaction was kept warm for 80 min. 45 g of ethanolamine was added to the reaction system, and the reaction was kept warm for 120 min. The temperature of the three-necked flask was increased to 90° C., and the solvent was evaporated under reduced pressure to obtain a modified polyurethane.
[0088] S3. Preparation of composite polyurethane solution
[0089] Weigh: 50g of nano-alumina powder, 20g of KH-570 and 500mL of anhydrous ethanol, add them into a three-necked flask, ultrasonically disperse for 50min, transfer the three-necked flask to a water bath with mechanical stirring, raise the temperature of the three-necked flask to 60°C, add 80mL of 3mol / L sodium hydroxide solution to the reaction system, keep warm and react for 80min, lower the temperature of the three-necked flask to room temperature, filter, wash the filter cake with purified water until it is neutral, and then drain it, transfer the filter cake to a drying oven at a temperature of 75°C, and vacuum dry it to constant weight to obtain modified alumina powder;
[0090] Weigh: 100 g of modified polyurethane and 800 mL of xylene are added to a three-necked flask and stirred. The temperature of the three-necked flask is raised to 100°C and stirred until the system is dissolved. 10 g of modified alumina powder and 0.1 g of chloroplatinic acid are added to the three-necked flask, and the reaction is kept warm for 8 hours. The temperature of the three-necked flask is lowered to room temperature, 400 mL of purified water is added to the three-necked flask and stirred for 15 minutes. The organic phase is allowed to stand and separate. The organic phase is washed 3 times with purified water, and the organic phase is dried over anhydrous sodium sulfate for 3 hours and then filtered. The filtrate is transferred to a rotary evaporator with a water bath temperature of 90°C, and part of the solvent is evaporated under reduced pressure to obtain a 55% composite polyurethane solution.
[0091] S4. Preparation of modified nylon fiber
[0092] Weigh: 50 g of nylon fiber, 40 g of dopamine hydrochloride, and 600 mL of deionized water, add them into a three-necked flask for ultrasonic dispersion, add tris(hydroxymethyl)aminomethane hydrochloride) into the three-necked flask, adjust the system pH to 8.5, stir and react at room temperature for 24 hours, filter, wash the filter cake with purified water until it is neutral and then dry, transfer the filter cake to a drying oven at 80°C, and vacuum dry it to constant weight to obtain modified nylon fiber.
[0093] S5. Preparation of casting material
[0094] Add o-cresol epoxy resin and xylene in a ratio of 2g:5mL into a three-necked flask and stir, raise the temperature of the three-necked flask to 90°C, stir until the system is dissolved, cool to room temperature, and obtain an epoxy resin solution for later use;
[0095] The composite polyurethane solution and the epoxy resin solution were added into a three-necked flask in a volume ratio of 8:7 and stirred for 30 minutes. The temperature of the three-necked flask was raised to 90° C., the solvent and low-boiling substances were evaporated under reduced pressure, and the material was discharged while hot to obtain a casting material precursor.
[0096] S6. Preparation of polyurethane sieve plate
[0097] Weigh: 700 g of a casting material precursor is heated until it is melted, 80 g of modified nylon fiber is added to the casting material precursor, and stirred and mixed for 5 minutes to obtain a casting material;
[0098] The temperature of the sieve plate mold is increased to 185°C, and the molten casting material is poured into the mold. The mold is closed after degassing, and the mold pressure is increased to 2MPa. The material is cured by heat preservation and pressure maintenance for 10 minutes to obtain a composite polyurethane sieve plate.
[0099] Comparative Example 1
[0100] The difference between this comparative example and Example 3 is that in step S1, octamethylcyclotetrasiloxane is used to replace cyclotetradimethylsiloxane and trifluoropropylmethylcyclotrisiloxane in equal amounts.
[0101] Comparative Example 2
[0102] The difference between this comparative example and Example 3 is that in step S3, the nano alumina powder in step S3 replaces the modified alumina powder used in the preparation process of the composite polyurethane solution.
[0103] Comparative Example 3
[0104] The difference between this comparative example and Example 3 is that step S4 is eliminated, and the modified nylon fiber in step S6 is replaced by the nylon fiber in step S4.
[0105] Comparative Example 4
[0106] The difference between this comparative example and Example 3 is that in step S5, no epoxy resin solution is added to the composite polyurethane solution.
[0107] Performance Test:
[0108] The hardness, tensile strength, elongation at break, tear strength, and relative volume abrasion loss of the composite polyurethane sieve plates prepared in Examples 1-3 and Comparative Examples 1-4 were measured with reference to the standard GB / T 33091-2016 "Polyurethane sieve plates";
[0109] The composite polyurethane sieve plate samples prepared in Examples 1-3 and Comparative Examples 1-4 were tested for resistance to 40 wt % sodium hydroxide and 8 mol / L hydrochloric acid with reference to the standard GB / T 3857-2017 "Test method for chemical resistance of glass fiber reinforced thermosetting plastics". The tensile strength and relative volume abrasion loss of the treated samples were measured.
[0110] According to the formula , the tensile strength retention rate of the test specimen, where Q 1 is the tensile strength of the sample after treatment with 40wt% sodium hydroxide or 8mol / L hydrochloric acid, Q 0 It is the tensile strength of the sample before treatment with 40wt% sodium hydroxide or 8mol / L hydrochloric acid;
[0111] According to the formula , calculate the relative volume wear growth of the sample (abbreviated as: wear growth), where V1 is the relative volume loss of the sample after treatment with 40wt% sodium hydroxide or 8mol / L hydrochloric acid, V 0 It is the relative volume abrasion of the sample before being treated with 40wt% sodium hydroxide or 8mol / L hydrochloric acid. The specific test results are shown in Table 1 below.
[0112] Table 1-Performance test data of samples
[0113]
[0114] Data Analysis:
[0115] Comparative analysis of the data in Table 1 above shows that the Shore hardness of the polyurethane sieve plate sample prepared by the present invention reaches 95.5A, the tensile strength reaches 38.1MPa, the tear strength reaches 89.2MPa, and the relative volume wear reaches 8.2mm 3 After the experiment of resistance to corrosion by 40wt% sodium hydroxide solution, the tensile strength retention rate reached 98.9%, and the wear increase was 2.0%. After the experiment of resistance to corrosion by 8mol / L hydrochloric acid, the tensile strength retention rate reached 99.4%, and the wear increase was 1.5%. The various test data of the embodiment are due to the comparative example, which shows that the present invention strengthens the modified polyurethane to prepare the composite polyurethane by modified aluminum powder, and then strengthens and cross-links it with o-cresol epoxy resin and modified nylon fiber, which not only effectively improves the wear resistance and mechanical strength of the polyurethane sieve plate material, but also improves its strong acid and alkali corrosion resistance, and effectively extends its service life.
[0116] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing a wear-resistant high-strength composite polyurethane sieve plate, characterized in that: The following steps are involved: S1. Add the modified polyurethane to xylene, raise the temperature of the reaction system to 90-100°C, stir until the system is dissolved, add the modified alumina powder modified with olefin double bonds and the catalyst to the reaction system, keep the temperature for 6-8h, and post-treat to obtain a composite polyurethane solution with a solid content of 45-55%; S2, adding epoxy resin solution to the composite polyurethane solution, stirring for 20-30 minutes, and post-processing to obtain a casting material precursor; S3, heating the castable precursor until the system is melted, adding modified nylon fiber to the castable precursor, stirring and mixing for 3-5 minutes, and obtaining a castable; S4, raising the temperature of the sieve plate mold to 175-185°C, pouring the casting material into the mold, closing the mold after degassing, raising the mold pressure to 1-2MPa, maintaining heat and pressure for 8-10 minutes, and discharging the material to obtain a composite polyurethane sieve plate; The preparation method of the modified polyurethane comprises the following steps: under the protection of an inert gas, adding a hydroxyl-terminated polysiloxane, polytetramethylene glycol, and a catalyst into xylene and stirring, raising the temperature of the reaction system to 65-75° C., dropping a diisocyanate solution into the reaction system, and after the dropping is completed, heat-retaining the reaction for 2-3 hours to obtain a polyurethane prepolymer solution, adding a chain extender into the polyurethane prepolymer solution, heat-retaining the reaction for 60-80 minutes, adding a capping agent into the reaction system, heat-retaining the reaction for 90-120 minutes, and post-treating the modified polyurethane; The preparation method of hydroxyl-terminated polysiloxane is as follows: cyclotetramethylsiloxane, trifluoropropylmethylcyclotrisiloxane, octamethylcyclotetrasiloxane and a catalyst are added to xylene and stirred, the temperature of the reaction system is increased to 115-125° C., the reaction is carried out by heat preservation for 2-3 hours, 1,3-bis(3-hydroxypropyl)-1,1,3,3-tetramethyldisiloxane is added to the reaction system, the reaction is carried out by heat preservation for 3-4 hours, and the hydroxyl-terminated polysiloxane is obtained by post-treatment; The preparation method of the modified nylon fiber is as follows: nylon fiber and dopamine hydrochloride are added to deionized water for ultrasonic dispersion, tris(hydroxymethyl)aminomethane hydrochloride) is added to the reaction system, the pH value of the system is adjusted to 8.5, the reaction is carried out at room temperature for 20-24 hours, and the modified nylon fiber is obtained by post-treatment.
2. The method for preparing a wear-resistant high-strength composite polyurethane sieve plate according to claim 1, characterized in that: In step S1, the dosage ratio of the modified polyurethane, xylene, modified alumina powder and catalyst is 10g:80mL:1g:0.01g, and the catalyst is chloroplatinic acid; in step S2, the volume ratio of the composite polyurethane solution and the epoxy resin solution is 8:7, and the epoxy resin solution is composed of o-cresol epoxy resin and xylene in a dosage ratio of 2g:5mL; in step S3, the weight ratio of the casting material precursor and the modified nylon fiber is 70:5-8.
3. The method for preparing a wear-resistant high-strength composite polyurethane sieve plate according to claim 1, characterized in that: The dosage ratio of the hydroxyl-terminated polysiloxane, polytetramethylene glycol, catalyst and xylene is 3g:7g:0.1g:30mL, the catalyst is dibutyltin dilaurate, the diisocyanate solution is composed of isophorone diisocyanate and xylene in a dosage ratio of 1g:2mL, during the synthesis of the polyurethane prepolymer, the molar ratio of isocyanate to hydroxyl is 1.1:1, the dosage ratio of the hydroxyl-terminated polysiloxane, chain extender and end-capping agent is 6g:1-1.5g:3g, the chain extender is 1,2,4-butanetriol, and the end-capping agent is ethanolamine.
4. The method for preparing a wear-resistant high-strength composite polyurethane sieve plate according to claim 1, characterized in that: The amount ratio of the cyclotetrasiloxane, trifluoropropylmethylcyclotrisiloxane, octamethylcyclotetrasiloxane and 1,3-bis(3-hydroxypropyl)-1,1,3,3-tetramethyldisiloxane is 3 mol:2 mol:5 mol:1 mol, the amount ratio of the octamethylcyclotetrasiloxane, the catalyst and xylene is 1 g:0.5 g:10 mL, and the catalyst is 55-60 wt % sulfuric acid.
5. The method for preparing a wear-resistant high-strength composite polyurethane sieve plate according to claim 1, characterized in that: The preparation method of modified alumina powder is as follows: adding nano alumina powder and KH-570 to anhydrous ethanol for ultrasonic dispersion for 30-50 minutes, stirring the reaction system, raising the temperature of the reaction system to 50-60°C, adding a catalyst to the reaction system, keeping the temperature for reaction for 60-80 minutes, and post-treating to obtain modified alumina powder, wherein the amount ratio of the nano alumina powder, KH-570, anhydrous ethanol and the catalyst is 5g:2g:50mL:8mL, and the catalyst is 2-3mol / L sodium hydroxide solution.
6. The method for preparing a wear-resistant high-strength composite polyurethane sieve plate according to claim 1, characterized in that: The usage ratio of the nylon fiber, dopamine hydrochloride and deionized water is 5g:3-4g:60mL.
7. A wear-resistant high-strength composite polyurethane screen plate, characterized in that: The wear-resistant high-strength composite polyurethane sieve plate is prepared by the preparation method of a wear-resistant high-strength composite polyurethane sieve plate according to any one of claims 1-6.
Citation Information
Patent Citations
Preparation method of MDI wear-resistant sieve plate
CN115160768A
High-elasticity oil-resistant and heat-resistant polyurethane board and preparation method thereof
CN106674995A
Wear-resistant polyurethane rubber industrial rubber roller and preparation method thereof
CN114656772A